"Changing behaviour, changing investment, changing operations": Using citizen science to inform the management of an urban river. Issue 3 (1st December 2019) - Cross, Iain D.
Abstract: Significant quantities of data are being collected by citizen scientists concerning environmental challenges. Networks of volunteers can collect data on spatial and temporal scales that may be beyond the resource and logistical capacities of the governmental bodies and other organisations that monitor and protect the environment. However, citizen science may be viewed with scepticism by decision makers and excluded from decision‐making because it is perceived as being of poor quality and lacking scientific credibility. This paper explores how citizen science has been used to inform the management of an urban river. It uses the example of the River Crane, a small urban river in London, UK, to demonstrate how data gathered through a volunteer project, Citizen Crane, supported decision‐making about the river. Through analysis of interviews with the project's leadership group, the paper examines how the project leadership team developed a high degree of credibility with stakeholders in the river management. This included drawing on the expertise of stakeholders to design the project and align the monitoring approaches with technical and scientific standards. Other factors of importance included open and professional communication between the Citizen Crane leadership team with regulators and businesses, and the development of shared understandings and expectations about the river's management. The leadership team drew on their professional experience to inform the design and management of the project, and to provide a conduit for data gathered by volunteer scientists to be embedded in decision‐making. The paper unpicks the ways in which citizen science challenges traditional notions of expertise in environmental decision‐making, and contributes to understanding how citizen science can support more legitimate and effective strategies for tackling complex socio‐environmental challenges. Abstract : Citizen science can significantly enhance decision‐making, but is often excluded because of concerns about the quality of data gathered by non‐expert volunteers. Citizen Crane, a citizen science project concerning an urban river in London, UK, significantly altered the management of the river due to the high‐quality, credible data gathered. The paper explores how working closely with the Environment Agency and water company enabled the project leadership team to influence the decision‐making about the River Crane and enhance the quality of the river.